Integrated proteomics and metabolomics analysis of D-pinitol function during hippocampal damage in streptozocin-induced aging-accelerated mice - Li, Xiaoxia; Gao, Yuan; Li, Baoying; Zhao, Wenqian; Cai, Qian; Yin, Wenbin; Zeng, Shudong; Li, Xiaoli; Gao, Haiqing; Cheng, Mei (Frontiers in Molecular Neuroscience, 2023)
Diabetes can cause hippocampal damage and lead to cognitive impairment. Diabetic cognitive impairment (DCI) is a chronic complication of diabetes associated with a high disability rate; however, its pathogenesis and therapeutic targets are unclear. We aimed to explore the mechanism of hippocampal damage during diabetes and evaluate the potential role of d-pinitol (DP) in protecting hippocampal tissue and improving cognitive dysfunction. DP (150 mg/kg/day) was administered intragastrically to streptozocin-induced aging-accelerated mice for eight weeks. Hippocampal tissues were examined using tandem mass tag (TMT)-based proteomics and liquid chromatography-mass spectrometry (LC-MS)/MS-based non-targeted metabolomic analysis. Differentially expressed proteins (DEPs) and differentially regulated metabolites (DRMs) were screened for further analysis, and some DEPs were verified using western blotting. Our results showed that 329 proteins had significantly altered hippocampal expression in untreated diabetic mice (DM), which was restored to This is a provisional file, not the final typeset article normal after DP treatment in 72 cases. In total, 207 DRMs were identified in the DM group, and the expression of 32 DRMs was restored to normal post-DP treatment. These proteins and metabolites are involved in metabolic pathways (purine metabolism, arginine and proline metabolism, and histidine metabolism), actin cytoskeleton regulation, oxidative phosphorylation, and Rap1-mediated signaling. Our study may help to better understand the mechanism of diabetic hippocampal damage and cognitive impairment and suggest a potential therapeutic target.